Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1161/circep.115.003226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Atrial Ablation Process and Strategy on Microemboli Formation During Irrigated Radiofrequency Catheter Ablation in an In Vivo Model

Abstract: Background-Formation of microemboli during catheter ablation has been suggested as a cause for asymptomatic cerebral emboli. However, it is unknown which part of the process and ablation setting/strategy is most strongly related to this occurrence. Methods and Results-A total of 27 pigs were used. Catheter/sheath manipulations in left atrium were performed in 25 of 27 pigs outfitted with microemboli monitoring systems. Ablations using open-irrigated radiofrequency catheters were performed in 18 of 25 pigs. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…In an elegant in vivo pig model Takami et al [16] performed different catheter, sheath manipulations and ablations while measuring micro-embolization using intracardiac echocardiography, Carotid Doppler, and an extra-corporal circulation loop which included a microbubble counter and blood filters to collect particulas. Significant microbubble formation was demonstrated on ICE, Carotid Doppler and in the loop during PV angiography and sheath flushing at a high flow, while micro-particles were mostly found during catheter dragging and after a steam pop.…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant in vivo pig model Takami et al [16] performed different catheter, sheath manipulations and ablations while measuring micro-embolization using intracardiac echocardiography, Carotid Doppler, and an extra-corporal circulation loop which included a microbubble counter and blood filters to collect particulas. Significant microbubble formation was demonstrated on ICE, Carotid Doppler and in the loop during PV angiography and sheath flushing at a high flow, while micro-particles were mostly found during catheter dragging and after a steam pop.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Takami et al 11 will benefit all those who perform this procedure. It provides us with useful strategies to mitigate microemboli formation and hopefully reduce ACE and stroke.…”
Section: Mercader Mitigating the Risk Of Microemboli During Ablationmentioning
confidence: 92%
“…In this issue of Circulation Arrhythmia and Electrophysiology, Takami et al 11 report which parts of the procedure during left atrial ablation are related to microbubble and microparticle formation. They elegantly characterize a series of procedures using open-irrigated radiofrequency catheters to determine the sequelae of left atrial radiofrequency ablations of pulmonary vein isolation.…”
Section: See Article By Takami Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…104 Stabile et al 105 also reported a very low complication rate of permanent sequelae in patients undergoing AF ablation with open irrigation catheters, thus making them a better choice for reducing the impact of neurological consequences during AF ablation. Takami et al 106 noted that during irrigated RF catheter ablation, formation of microbubbles was the greatest during fast saline/contrast injections and steam pops, Relevant reduction for all rates when using periprocedural continued effective oral anticoagulants (warfarin or novel oral anticoagulation agents). SCE: silent cerebral event; MRI: magnetic resonance imaging.…”
mentioning
confidence: 99%